ANALISIS PENDIDIKAN SENI MUSIK SEBAGAI SARANA TERAPI EDUKATIF TERHADAP KESEHATAN MENTAL ANAK SEKOLAH DASAR - Jaka Nugraha; Eris Risnawati; Dede Muhtar Safari; Reza Maulana (Politeknik Negeri Jakarta, 2025)
Abstract This study aims to analyze the role of music education as an educational therapeutic medium in supporting the mental health of elementary school children. The background of this research is based on the increasing cases of stress, anxiety, and negative emotional behavior among elementary school-aged children due to academic pressure and the lack of positive means for self-expression. The research method used is descriptive qualitative, with data collection techniques including observation, in-depth interviews with music teachers and school counselors, as well as documentation of learning activities. The results of the study show that music learning activities designed in an educational manner can foster self-confidence, reduce anxiety levels, improve social skills, and strengthen empathy among students. Music serves as a medium for emotional expression as well as an effective means of self-regulation. In conclusion, music education has great potential as an educational therapy that supports the mental health of elementary school children, especially when implemented in a planned, collaborative, and sustainable manner. Keywords: music education, educational therapy, mental health, elementary school children.